GAOK AS A UNIQUE CULTURAL AND RELIGIOUS IDENTITY EXPRESSION FROM MAJALENGKA, WEST JAVA - Mahmudah Nur; Asri Saraswati (Center for Research and Development of Religious Literature and Heritage, 2023)
This article presents an explorative study on the continuity of Gaok traditions amidst social change in Majalengka, West Java, Indonesia. As a cultural heritage, Gaok faced a negative stigma as a bid’ah (heresy). This article investigates how the Gaok serves as a religious expression as well as a form of adaptation for survival. It also explores how Gaok represents the unique religious identity of the Majalengka people with the fusion of Sundanese and Javanese cultures. A folklore approach was employed in this study, involving the texts of manuscripts performed in Gaok, observation of Gaok performances, and interviews with Gaok performers. The study found that Gaok represents the oral religious expressions of the Majalengka people, which contain collective memories about their cultural values, identity, and history. Furthermore, Gaok is an adaptive tradition to the contemporary developments over time, primarily cultural and religious influences in Majalengka. As an oral tradition, Gaok has transformed from participatory and communal art to individual performances.